Editor’s Note: Volume XIV No. I - Calise, Isabella (Bellarmine Law Society Review, 2024)
It is with sincere gratitude and excitement that I welcome you to the inaugural issue of the Bellarmine Law Society Review's fourteenth edition. We are thrilled to present to you an array of insightful and thought-provoking pieces that delve into pressing issues at the intersection of law, society, and technology. In this edition, authors Caroline Corcoran, Francis Hodgens, and Joseph Murphy offer compelling examinations of contemporary legal challenges, each shedding light on different facets of our evolving legal landscape. First, rising senior Caroline Corcoran succinctly delves into the nuanced interpretation of threats under federal law, focusing on the landmark case of Elonis v. United States. Through meticulous analysis, Corcoran navigates the complexities of First Amendment rights, intent, and the objective assessment of threatening communications, ultimately highlighting the delicate balance between free speech protections and addressing potential risks. Next, class of 2024 graduate Francis Hodgens confronts the housing affordability crisis gripping Greater Boston, dissecting decades of poor land use planning and its profound impact on housing production and affordability. Hodgens's analysis of the MBTA Communities Act offers a critical evaluation of its potential to address the challenges associated with housing affordability, providing policymakers with essential recommendations for ensuring its success. Finally, rising junior Joseph Murphy tackles the intricate matter of liability in the era of self-driving cars, examining the shifting dynamics of responsibility amidst the increased implementation of autonomous vehicles. Murphy's work challenges misconceptions surrounding automation levels in these vehicles and underscores the imperative for tort liability law to adapt to the evolving automobile landscape. As we embark on this intellectual journey, Managing Editor Tommy Dee and I extend our sincerest congratulations and gratitude to the seniors of the class of 2024, including our esteemed authors over the years, our dedicated associate editor Louis Barber, and, of course, many of our valued readers. Your contributions and commitment have made this edition possible, and we are honored to have these impressive investigations of the law open up the first issue of the 2024 year. Now, I invite you to delve into the richness of these scholarly contributions and engage in the critical conversations they inspire.